Therapeutic approaches for the treatment of renal disease in juvenile systemic lupus erythematosus: an international multicentre PRINTO study. Issue 9 (25th October 2012) - Miettunen, Paivi M; Pistorio, Angela; Palmisani, Elena; Ravelli, Angelo; Silverman, Earl; Oliveira, Sheila; Alessio, Maria; Cuttica, Ruben; Mihaylova, Dimitrina; Espada, Graciela; Pasic, Srdjan; Insalaco, Antonella; et al.
Abstract : Objectives: To evaluate therapeutic approaches and response to therapy in juvenile systemic lupus erythematosus (SLE) with renal involvement in a large prospective international cohort from four geographic areas. Methods: New onset and flared patients with active renal disease (proteinuria ≥0.5 g/24 h) were enrolled in 2001–2004. Therapeutic approaches and disease activity parameters were analysed at baseline, 6, 12 and 24 months. Response was assessed by the PRINTO/ACR criteria. Results: 218/557 (79.8% female subjects, 117 new onset and 101 flared) patients with active renal disease were identified; 66 patients were lost to follow-up and 11 died. Mean age at disease onset for new onset group was higher than for flared group (13.1 vs 10.2 years, p<0.0001). At baseline, both groups had similar renal activity with similar median doses of corticosteroids (1.0–0.76 mg/kg/day). Cyclophosphamide (43.1%) and azathioprine (22%) were the most common immunosuppressive drugs. At baseline, South American patients received higher doses of corticosteroids than in other areas in new onset (median 1.16 vs 0.8–1 mg/kg/day) while cyclophosphamide use was similar in all four regions in the new onset group. There were no differences regarding the use of azathioprine or mycophenolate mofetil worldwide. PRINTO 70 response was reached in a greater percentage of new onset versus flared patients (74.8% vs 53.3%; p=0.005) at 6 months while at 24 months ACR 90 was reached by 69.9% and 56.1%, respectively. Conclusions: New onset and flared juvenile SLE improved similarly over 24 months with minimal differences in therapeutic approaches worldwide.